(untitled) (International Journal of Engineering and Computer Science, 2017)
There is a great popularity achieved by Wireless Mesh Networks in the recent years due to their last mile Internet access, low deployment cost and self-configuring features. It is considered to be an effective solution to support multimedia services in last miles due to their automatic configuration and low cost deployment. The main feature of WMNs is multi-hop communications which may result in increased coverage, better robustness and more capacity. Implemented on limited radio range wireless media, WMNs bring about many challenges such as effective media access control, efficient routing, quality of service provisioning, call admission control and scheduling. The various performance measurements based on reported result analysis use various optimal metrics for energy efficient wireless communication system. The energy efficient wireless communication protocols that are being used in the current work includes viz. data transfer rate, packet size, protocol used, energy efficiency, number of nodes, square topology area, distance between nodes and base station. The parameters achieved during simulation for prototype design of energy efficient network initiated with 300 nodes, clustered into 30 each forming such 10 major clusters, distance between clusters is maintained up to 200m, with 50 iterations/rounds the data packets received is up to 16kbps within the clusters, with square topology area of 1250mx1250m and, power consumption of up to24dB.